Critical Thinking Skill In Science On Junior High School By Problem Based Learning Models - Reni Ikayanti; Suratno Suratno; Dwi Wahyuni (Pancaran Pendidikan, 2017)
The purpose of this study was to determine the effectiveness of PBL learning model development effectiveness and results of critical thinking ability to learn science in a small-scale test (10 students) and large-scale test of class VII C totaling 34 students of SMP Negeri 1 Lumajang semester of the 2016-2017 academic year even. Data collection techniques used include Model validation, questionnaire, Observation, and Test.Analisis data used in this study using descriptive quantitative. The results showed that the application of PBL learning model with Takrir can improve the ability of critical thinking and science learning outcomes of students SMP Negeri 1 Lumajang. The average percentage of validation models and learning tools from experts (lecturers) and users 88.9% (Valid). Results increased students' critical thinking skills from questionnaire results and 85% observation and 82% student learning outcomes.